(3OQGSI GdLOhi GdEbJUGOjI hJbjje caGAI COGA GdefXeGJ (B/s - (3GddhRj, SdjeGfs; (3Cd GOe, jhMfGs ((3YeGf(B: s (3OGQ GdeSjQI ddfTQ hGdJhRjY(B, s, 2005)
(3eaghe GdeTQhY GdEbJUGOj(B-(3CSGdjH YedjI GJNGP GdbQGQGJ GdESJKeGQjIs
Keywords: (3GdLOhi GdEbJUGOjIs; (3GdeTQhYGJ GdEbJUGOjIs